Bouveret syndrome, a rare form of gallstone ileus. Case report. - Lúver Alexi Macías Jara; David Cipriano Yépez Yépez; José Ramon Chung Villavicencio; Marcos Alvarado Villegas; Adriano Rocha Galecio (Case Reports)
Introduction: Bouveret syndrome is a rare form of gallstone ileus that causes gastric obstruction due to the presence of a gallstone in the pylorus or duodenum, secondary to biliodigestive fistula. This condition is difficult to diagnose and one of its main complications is hemorrhage in the digestive tract. Two-stage surgical management is recommended, although it can also be managed through upper endoscopy in gallstones smaller than 2.5cm. Prognosis and postoperative period are good.